Chaos-generating periodic orbits of topological defects in confined active nematics - Brandon Klein; Alejandro J. Soto Franco; Md Mainul Hasan Sabbir; Matthew J. Deutsch; Ross Kliegman; Robin L. B. Selinger; Kevin A. Mitchell; Daniel A. Beller (Proceedings of the National Academy of Sciences, 2026)
Active nematics in two dimensions stir themselves efficiently through internally generated chaotic flows, largely driven by motile + 1 / 2 disclinations.We investigate how this tendency toward chaotic fluid stirring can, counterintuitively, produce certain ordered, periodic flows in confinement, characterized by stable periodic orbits of + 1 / 2 disclinations. We computationally study two-dimensional active nematics in systems with boundary conditions requiring a prescribed number n of excess + 1 / 2 disclinations, using Beris-Edwards nematohydrodynamics simulations alongside an agent-based simulation approach. We find that when confinement is sufficiently strong to prevent defect pair-nucleation, but not strong enough to arrest all flow, then n = 3 defects generically follow a “golden braid” orbit as observed recently in experiments, and we predict a “silver braid” orbit of n = 4 defects. For these results and for greater numbers of defects, we show that the periodic or chaotic nature of the dynamics is determined by a balance between the number of defects and the number of vortices in the flow field, suggesting a design criterion for ordered flows in active nematics.